The conserved amino-terminal domain of hSRP1 alpha is essential for nuclear protein import. - Weis, K (1996)
Nuclear proteins are targeted through the nuclear pore complex (NPC) in an energy-dependent reaction. The import reaction is mediated by nuclear localization sequences (NLS) in the substrate which are recognized by heterodimeric cytoplasmic receptors. hSRP1 alpha is an NLS-binding subunit of the human NLS receptor complex and is complexed in vivo with a second subunit of 97 kDa (p97). We show here that a short amino-terminal domain in hSRP1 alpha is necessary and sufficient for its interaction with p97. This domain is conserved in other SRP1-like proteins and its fusion to a cytoplasmic reporter protein is sufficient to promote complete nuclear import, circumventing the usual requirement for an NLS receptor interaction. The same amino-terminal domain inhibits import of NLS-containing proteins when added to an in vitro nuclear transport assay. While full-length hSRP alpha is able to leave the nucleus, the amino-terminal domain alone is not sufficient to promote exit. We conclude that hSRP1 alpha functions as an adaptor to tether NLS-containing substrates to the protein import machinery.